The Jaipongan Drumming Strokes in Lagu GedÃƒÂ© in Sundanese Gamelan - Saepudin, Asep; Yulaeliah, Ela (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This paper aims to describe the Jaipongan drumming strokes in Lagu GedÃƒÂ©. Lagu GedÃƒÂ© is a type of song in Sundanese Karawitan that has a large embat (rhythm). This song includes a dish of drums vocals accompanied by gamelan pelog-salendro with characteristics that have tone, barrel, surupan, embat, gending, slow tempo, embat opat wilet, and bound by the standard rules. Observations were made by appreciating JaiponganÃ¢â‚¬â„¢s performances in Bandung and Karawang. Besides, the author conducts interviews with several primary informants who are directly involved in the arrangement of Jaipongan. GedÃƒÂ©Ã¢â‚¬â„¢s point here is to look at it with a smooth, soft, slow serving. The Kiliningan genre has a specific punch motif name for GedeÃ¢â‚¬â„¢s song.Ã‚Â The name of this variation is called tepak melem. Melem has a delicious or gentle meaning. Tepak melem to accompany Sekar Gending songs in Kiliningan genre. The phenomenon that happens that Lagu Gede is served in Kiliningan dish and used to attend Jaipongan dance. When JaiponganÃ¢â‚¬â„¢s work uses GedÃƒÂ©Ã¢â‚¬â„¢s song, it generates innovations. GedÃƒÂ©Ã¢â‚¬â„¢s song is no longer presented with a glued drum but with a tepak diteunggeul. Diteunggeul contains the meaning of being hit hard, powerful, dynamic, and fast. This research concluded that jaipongan drumming strokes in Lagu GedÃƒÂ© is realized that drummers and dancers must explore many spaces because it has the freedom to work. After all, they present it in an embat opat wilet (big rhythm). This affects the widening of the number of beats, the position of kenongan, pancer, and gongan. Artists have the freedom to do creativity in working on GedeÃ¢â‚¬â„¢s songs.Ã‚Â The space of artists in their work can ultimately foster new creativity that impacts the growth and development of Sundanese karawitan.